Formal Structure of the Text – enquiry into the chapter, the title and the introduction in Julius Zeyer`s prose style. - Schacherl, Martin (Slavia Occidentalis, 2017)
This paper analyses three aspects (the chapter, the title and the introduction ) of prose by Julius Zeyer, a Czech poet. My explicit goal is to seek a relation between the specific forms of the text’s horizontal arrangement and its narrative rhythm as deduced from a comprehensive approach to the author’s works. The analysis relies on a presumption that in fiction, even the horizontal arrangement of a specific literary work is submitted to the function of aesthetic communication.